Development Learning Media Mathematics Game Board Triple-F (Fraction For Fun) to Improve Understanding of the Material Various Forms of Fractions - Khumairo, Dahlia; Yuliandari, Ria Norfika (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
The aim of this research is to produce learning media and explain the effect of using learning media to improve students' understanding. The research method in this study is Research & Development with Sugiyono’s development model. The technique of collecting data used questionnaires, observation, interviews, and documentation. The data obtained quantitative and qualitative descriptions. The research samples are 4th-grade students of MINU Maudlu’ul Ulum Malang. The result of the research and development these learning media are: 1) the design of learning media Triple-F (Fraction for Fun) that game board form, that is packed in the box size 31x25 cm and consists of the game board, question card, instruction of use, dice and point. Based on the result of validation, show that media is achieved valid category, the result of validation media expert 90%, content expert 68%, learning expert 95%, 3) the effectiveness level of developed media can be seen from value of pre-test 64,5 and post-test 82,2 it is indicated that the result is significant, and questionnaire of students interest reach 91,6%, it means that the learning media mathematics board game Triple-F can improve the understanding of material various form of fraction.